ITGAL as a prognostic biomarker correlated with immune infiltrates in melanoma - Deng, TengFei; Wang, Chaoyong; Gao, Cong; Zhang, Qiang; Guo, Jun (Frontiers in Oncology, 2023)
This study investigates the relationship between ITGAL expression and immune infiltration, clinical prognosis, and specific types of T cells in melanoma tissue sections. The findings reveal the key role of ITGAL in melanoma and its potential mechanism of regulating tumor immune infiltrating cells, highlighting its potential as a diagnostic target for this type of cancer.